Evaluating Multi-Species Cover Crops for Forage Production - C. Davis; DeAnn Presley; J. K. Farney; Gretchen Sassenrath (Kansas Agricultural Experiment Station Research Reports, 2016)
Cover crops offer potential benefits for improving soil health, but establishment and management costs can be expensive. One way for farmers to recover these costs is to graze the forage, which benefits producers by integrating crop and animal production. More information is needed on the potential forage quantity and quality for grazing livestock of cover crops and mixed species of cover crops. Researchers have suggested that different plant species complement each other, but additional work is needed to determine how best to balance forage production and how competitive the various species are when added to a mix. Sixteen treatments were drill-seeded at the Southeast Research and Extension Center near Columbus, Kansas, in August 2014 and 2015. Each treatment consisted of a three-way mix representing popular cover crops from the plant families Brassicaceae (brassicas), Poaceae (grasses), and Fabaceae (legumes). Eight species were planted, including forage radish (Raphanus sativus), purple-top turnip (Brassica rapa), oat (Avena sativa), rye (Secale cereale), barley (Hordeum vulgare), wheat (Triticum aestivum), Austrian winter pea (Pisum sativumsubsp.arvense), and berseem clover (Trifolium alexandrinum). Small areas of each plot were clipped at 45-, 74-, and 91-day intervals each year. The clipped biomass was then weighed, sorted, and dried to determine biomass as well as species composition. In 2014 the average biomass produced at 45, 74, and 91 days was 1,250, 3,290, and 3,050 lb/ac, respectively. These range from 470–1,940 lb/ac 45 days after planting to 1,790–4,440 lb/ac at 91 days after planting, depending on the cover crop mix. In 2015, the average biomass at 45, 74, and 91 days was 1,120, 1,604, and 2,273 lb/ac, respectively. These range from 557-1,876 lb/ ac 45 days after planting to 1,100–4,127 lb/ac at 91 days after planting, depending on the cover crop mix.
Keywords: cover crops